A new strategy for short-term ramp rate control in wind farms. (September 2020) - Probst, Oliver
Highlights: Drops in wind power can be efficiently mitigated with short-term power forecasts. An analytical framework has been developed to assess this potential. Power not delivered is minimal compared to traditional curtailment approaches. The impact of forecast uncertainties has been assessed analytically. Numerical simulations with synthetic and real wind farm data confirm the results. Abstract: Short-term drops in power output of wind farms may be a serious impediment to large-scale wind energy deployment in weak systems such as island grids. As opposed to operational measures countering this problem by generalized or flat curtailment, a novel approach based on short-term power forecasts is proposed in the present work. Analytical expressions for compliance with a given yet variable slope limit, achievable through Forecast-Based Curtailment (FBC), are derived for forecasts of varying accuracy. The cost-benefit relations of flat curtailment vs. FBC are compared. Output power change distributions used in this work are shown to be consistent with observational data from an operational wind farm. Numerical simulations based on both synthetic and operational wind farm data confirm the accuracy of the analytical expressions derived in this work.